Airports and automation proceedings of the 9th World Airports Conference organized by the Institution of Civil Engineers and held in London on 10-12 September 1991 - Crook, G. M. (Thomas Telford, 1992)
This volume covers the latest developments in airport-related technology. In the light of ever-increasing traffic through airports the international authors present the latest developments that strive continually to improve the safe functioning and efficiency of airports.